Magnetic Field Enhanced Photoreduction of Cr (Vi) over the P-N-P Bifeo3/Cofe2o4/Co3o4 Nanocomposites - Casagrande-Denardin, J; Radhalayam, D (Elsevier B.V., 2022)
This study shows a highly efficient photoreduction of heavy metal Cr (VI) in water by applying external magnetic field (MF) to the p-n-p ternary BiFeO3/CoFe2O4/Co3O4 (BFO/CFO/CO) nanocomposites under visible light irradiation. A series of bismuth ferrite (BiFeO3: BFO), cobalt ferrite (CoFe2O4: CFO), cobalt oxide (Co3O4: CO), BFO/CFO and BFO/CFO/CO nanocomposites have been synthesized by hydrothermal method. The prepared samples were characterized for their size, morphology, structural, optical and magnetic properties. Compared with the individual BFO, CFO, CO, and binary BFO/CFO, the as-prepared ternary BFO/CFO/CO nanocomposites exhibited an enhanced photoreduction towards the Cr (VI). Moreover, BFO/CFO/CO nanocomposites showed increased reduction efficiency (99.3 %) when a magnetic field of 0.4 T was applied during the process. The kinetic rate constant of ternary nanocomposite in the presence of the MF was calculated as 0.1316 min−1, which is almost 4.95 times higher than BFO/CFO/CO in the absence of the MF. The enhanced reduction could be related to the MF accelerated separation of electron-hole pairs and their transfer through the interfaces. Further, the stability of the synthesized samples and reproducibility of MF catalytic systems were also investigated. © 2022 Elsevier B.V.